Ciri-ciri asas beberapa tanah yang dikisar - Mohd Raihan Taha; Lim, Sook Yee; Zamri Chik (Penerbit UKM, 2009)
Laboratory experiments were conducted to study the fundamental properties of kaolinite, montmorillonite and a UKM soil at nano levels. SEM analysis showed that much more nano size particles were obtained after the milling process. Testings and comparison of the properties of kaolinite, montmorillonite and UKM soil with regard to its liquid limit, plastic limit, plasticity index, specific surface, pH and specific gravity at the normal and after crushing were then conducted. Laboratory tests results showed that the values of liquid limit, plastic limit, specific surface and specific gravity of soil/clay were higher after crushing, but its pH and plasticity index were lower compared to the initial soil samples. The results of soil strength test showed that when the percentage of crushed particles in the soil/clay is increased, the strength of the soil/clay will also be increased. Thus, crushed soil/clay or nanoparticles are potentially suitable for changing and improving the properties of soil/clay for various applications.